تأثير وسائل الاعلام في بناء الهوية الوطنية للطالب الجامعي الليبي دراسة استطلاعية لطلبة كلية التربية زوارة (Comprehensive Journal of Science, 2026)
The study aimed to identify the functions performed by media in building the national identity of Libyan university students and to determine the most influential media channels in strengthening national identity among students of the Faculty of Education at the University of Zuwara. The study adopted the descriptive-analytical approach, which allows for describing the reality of students’ media consumption and analyzing its impact on national identity. The research population consisted of all students of the Faculty of Education at the University of Zuwara, and a stratified random sample of 80 students was selected to ensure representation of different categories (gender, academic year, and specialization). A questionnaire was used, consisting of four main dimensions (traditional and digital media, level of awareness and national attitudes, national identity, and behaviors). The validity of the instrument was confirmed through expert judgment, and its reliability was verified using Cronbach’s alpha coefficient.The results showed that students’ ages ranged between 19 and 21 years, with the majority belonging to low and middle income groups, and more than 80% being unmarried. The findings also revealed that students followed media for more than three hours daily, with digital media and television being the most influential. Most students believed that media plays a significant role in enhancing national identity, especially through Instagram and TikTok platforms, with 62.5% engaging intensively. Additionally, 62.3% considered the media to be very successful in strengthening national identity, while 10.6% criticized its lack of success.The study recommended increasing the production of national cultural and educational content, enhancing objectivity and transparency, utilizing social media platforms for national campaigns, involving students in content creation, and conducting periodic research to evaluate media influence.